Using viral gene sequences to compare and explain the heterogeneous spatial dynamics of virus epidemics. - Dellicour, S; Rose, R; Faria, N; Vieira, L; Bourhy, H; Gilbert, M; Lemey, P; Pybus, O (Oxford University Press, 2017)
Rabies is an important zoonotic disease distributed worldwide. A key question in rabies epidemiology is the identification of factors that impact virus dispersion. Here we apply new analytical methods, based on phylogeographic reconstructions of viral lineage movement, to undertake a comparative evolutionary-epidemiological study of the spatial dynamics of rabies virus (RABV) epidemics in different hosts and habitats. We compiled RABV data sets from skunk, raccoon, bat and domestic dog populations in order to investigate the viral diffusivity of different RABV epidemics, and to detect and compare the environmental factors that impact the velocity of viral spread in continuous spatial landscapes. We build on a recently developed statistical framework that uses spatially- and temporally-referenced phylogenies. We estimate several spatial statistics of virus spread, which reveal a higher diffusivity of RABV in domestic dogs compared with RABV in other mammals. This finding is explained by subsequent analyses of environmental heterogeneity, which indicate that factors relating to human geography play a significant role in RABV dispersion in domestic dogs. More generally, our results suggest that human-related factors are important worldwide in explaining RABV dispersion in terrestrial host species. Our study shows that phylogenetically informed viral movements can be used to elucidate the factors that impact virus dispersal, opening new opportunities for a better understanding of the impact of host species and environmental conditions on the spatial dynamics of rapidly evolving populations.